The short-term impact of high energy nutritional supplements on energy balance in underweight primi-gravidae; a randomized controlled trial - Tariq, Kalsoom; Fatima, Sadia; Nazli, Rubina; Habib, Syed Hamid; Shah, Mohsin (Journal of the Pakistan Medical Association, 2023)
Objectives: To determine the impact of high-energy nutritional supplements on appetite, appetite regulators, energy intake and macronutrients level among underweight primigravidae. Method: The single-blind randomised controlled trial was conducted from April 26, 2018, to August 10, 2019, in tertiary care hospitals of Khyber Pakhtunkhwa province of Pakistan, after approval from the ethics review committee of Khyber Medical University, Peshawar, and comprised underweight primigravidae who were randomly allocated to high energy nutritional supplement group A and placebo group B. Appetite questionnaires were filled and blood samples were obtained in fasting state, at 30, 60, 120, 210 and 270 minutes to measure blood glucose, insulin, peptide YY and cholecystokinin. Breakfast and lunch were served at 30 minutes and 210 minutes after supplementation, respectively. Data was analysed using SPSS 20. Results: Of the 36 subjects, 19(52.8%) were in group A and 17(47.2%) were in group B. The overall mean age was 18.66 ± 2.5 years. Energy intake in group A was significantly higher than group B (p<0.001), and so were mean protein and fats (p<0.001). The subjective appetite perceptions for ‘hunger’ and ‘desire to eat’ were significantly lower (p<0.001) before lunch in group A. Plasma concentrations of appetite hormones corresponded to the appetite perceptions and were significantly higher in group A after breakfast and lunch for peptide YY, cholecystokinin and insulin compared to group B (p<0.001). Conclusion: High-energy nutritional supplement was found to have short-term suppressive effect on energy intake and appetite. Trial registration: ClinicalTrials.gov Identifier: ISRCTN 10088578. Registered on 27 March 2018. https://www.isrctn.com/ISRCTN10088578. Key Words: Primigravida, Supplements, Energy, Macronutrients, Appetite, Appetite regulators.